Kozier and Erb's fundamentals of nursing : concepts, process and practice - Berman, Audrey; Snyder, Shirlee J. ;Frandsen, Geralyn (Upper Saddle River, New Jersey : Pearson Prentice Hall, 2022)
Addresses the concepts of contemporary professional nursing. These concepts include but are not limited to caring, wellness, health promotion, disease prevention, holistic care, multiculturalism, nursing theories, nursing informatics, nursing research, ethics, and advocacy.
unit 1. The Nature of nursing -- ch. 1. Historical and contemporary nursing practice -- ch. 2. Nursing education, research, and evidence-based practice -- ch. 3. Nursing theories and conceptual frameworks -- ch. 4. Legal aspects of nursing -- ch. 5. Values, ethics, and advocacy -- unit 2. Contemporary health care -- ch. 6. Health care delivery systems -- ch. 7. Community nursing and care continuity -- ch. 8. Home care -- ch. 9. Nursing informatics -- unit 3. The nursing process -- ch. 10. Critical thinking and the nursing process -- ch. 11. Assessing -- ch. 12. Diagnosing -- ch. 13. Planning -- ch. 14. Implementing and evaluating -- ch. 15. Documenting and reporting -- unit 4. Health beliefs and practices -- ch. 16. Health promotion -- ch. 17. Health, wellness, and illness -- ch. 18. Culture and heritage -- ch. 19. Complementary and alternative healing modalities -- unit 5. Life span development -- ch. 20. Concepts of growth and development -- ch. 21. Promoting health from conception through adolescence -- ch. 22. Promoting health in young and middle-aged adults -- ch. 23. Promoting health in elders -- ch. 24. Promoting family health Unit 6. Integral aspects of nursing -- ch. 25. Caring -- ch. 26. Communicating -- ch. 27. Teaching -- ch. 28. Leading, managing, and delegating -- unit 7. Assessing health -- ch. 29. Vital signs -- ch. 30. Health assessment -- unit 8. Asepsis -- ch. 32. Safety -- ch. 33. Hygiene -- ch. 34. Diagnostic testing -- ch. 35. Medications -- ch. 36. Skin integrity and wound care -- ch. 37. Perioperative nursing -- unit 9. Promoting psychosocial health -- ch. 38. Sensory perception -- ch. 39. Self-concept -- ch. 40. Sexuality -- ch. 41. Spirituality -- ch. 42. Stress and coping -- ch. 43. Loss, grieving, and death -- unit 10. Promoting physiologic health -- ch. 44. Activity and exercise -- ch. 45. Sleep -- ch. 46. Pain management -- ch. 47. Nutrition -- ch. 48. Urinary elimination -- ch. 49. Fecal elimination -- ch. 50. Oxygenation -- ch. 51. Circulation -- ch. 52. Fluid, electrolyte, and acid-base balance --
Includes index.
Keywords: NURSING